The possible contribution of postal service sector to city logistics - Zelenska, Ina; Švadlenka, Libor (University of Pardubice, 2018)
The use of traditional postal services is constantly decreasing, prompting the management of postal service providers to look for new opportunities for utilization of available resources and developing the postal service sector. Simultaneously the city logistics experts are looking for a way to ensure sustainable development of the urban areas and fulfill increasing delivery requirements within the city. In Czech and European literature, there is no publication focusing on the interconnection of these two sectors, i.e. postal service sector and the city logistics. Foreign literature provides a number of papers related to the possibility of cooperation between the postal service sector and the city logistics. The analysis of these papers and the proposal of possible solutions respecting local conditions in the Czech Republic is the aim of the paper.
Keywords: postal services; city logistics; reverse logistics; urban consolidation centre